ARAHAN JALUR LALU LINTAS YANG AMAN BAGI PENGENDARA SEPEDA (STUDI KASUS:PEKERJA BERSEPEDA DI JALAN RAYA KALIGAWE) - Destriane, Natalia (Universitas Diponegoro, 2009)
Road as transportation infrastructure must be adaptive for the users. However, along with the outgrowth of automotiveindustry, people start to leave non-motorized vehicle. Nowadays road merely serves and accommodates motorized vehicle. Roadphysical design is unable to accommodate the un-motorized vehicle necessity such as bicycle. The cyclists are forgotten that they arealso road users as what happens in Kaligawe Street, Semarang in which cycling inconvenience becomes an important issue. Thedemand of secure traffic lane by cyclists is very high which since Kaligawe Street as arterial road has threatened the safety of cyclists.This study aims to arrange the secure traffic lane designed for cyclists by utilizing the traffic and slow lane which are designed basedon the change of driverâs behavior in order to ensure all road users safety.